A Test Environment for Wireless Hacking in Domestic IoT Scenarios - Muñoz-Gallego, Antonio Jesús; Fernández-Gago, María del Carmen; López-Villa, Roberto (Springer Nature, 2022)
Security is gaining importance in the daily life of every citizen. The advent of Internet of Things devices in our lives is changing our conception of being connected through a single device to a multiple connection in which the centre of connection is becoming the devices themselves. This conveys the attack vector for a potential attacker is exponentially increased. This paper presents how the concatenation of several attacks on communication protocols (WiFi, Bluetooth LE, GPS, 433 Mhz and NFC) can lead to undesired situations in a domestic environment. A comprehensive analysis of the protocols with the identification of their weaknesses is provided. Some relevant aspects of the whole attacking procedure have been presented to provide some relevant tips and countermeasures.
Keywords: Redes de ordenadores; Seguridad informática; Sistemas de comunicaciones inalámbricos; Sistemas de comunicaciones móviles; IoT security; Domestic security; Network security; Hacking the IoT